Analysis of Policy Implementation of Minimum Service Standards in the Field of Health Indicators of Health Services for People with Diabetes Mellitus in Magelang Regency - Agustina, Nika Maya; Mahendradhata, Yodi; Putri, Likke Prawidya (Jurnal Kebijakan Kesehatan Indonesia, 2023)
In order to overcome diabetes, the government set some laws and regulations. One of them is Government Regulation Number 2 of 2018 concerning minimum service standards. SPM for Health is regulated in Permenkes number 4 of 2019. District / City Health SPM consists of 12 indicators. One of the indicators is health care in patients with diabetes mellitus according to the standard. Magelang regency is the third lowest Regency in 2020 with achievements of only 41.9 percent and 59.75 percent in 2021. Necessary analysis related factors inhibiting and supporting implementation. This study was conducted by the method of Qualitative content analysis. Using in-depth interview techniques, field observation and secondary data retrieval.The results of the study there are variations between the achievement of SPM Puskesmas. factors inhibiting the achievement of SPM in the field of health indicators of health services in patients with diabetes mellitus in Magelang regency is the lack of availability of budget, infrastructure and Human Resources, community characteristics and lack of understanding and knowledge both from the organizers and users. Supporting factors for the achievement of SPM in the field of health indicators of health services for people with diabetes mellitus in Magelang regency are leadership support and the chosen policy strategy.